Variability levels of selected amino acids among mandarins produced in Uruguay - Rezende, Sofía; Banchero, Sabrina; Migues, Ignacio; Cesio, María Veronica; Rivas, Carlos Fernando; Heinzen, Horacio; Besil, María Natalia (Eclética Química, 2021)
Nutraceutical properties of mandarins are of great interest to promote their consumption. The occurrence of free amino acids in foods is relevant to assess the nutritional value of it. To learn more about the amino acids’ occurrence and variability between species, a targeted metabolomics study in ‘Ellendale’, ‘Willowleaf’ and ‘Page’ varieties was performed through ion exchange liquid chromatography coupled to tandem mass spectrometry. The studied amino acids were asparagine, glutamic acid, glutamine, histidine, methionine, phenylalanine, proline, threonine and tyrosine. The difference between two consecutive seasons was evaluated, as well as the influence of fruit maturity of ‘Page’ collected in two periods of 2015. The analytical methodology was validated. The concentration of the compounds through principal component analysis, separated well apart the three cultivars in both harvests, showing a particular profile for each of them. When comparing mature and immature cultivar ‘Page’, the amino acids with higher levels in mature samples were histidine, asparagine, glutamine and glutamic acid. The profiles were different due to genetic diversity, and the climatic conditions. These results add value to citric production.